Designed nucleus penetrating thymine-capped dendrimers: a potential vehicle for intramuscular gene transfection. Issue 46 (30th October 2015) - Yan, Jia-Ying; Liu, Chia-Yeh; Wu, Zong-Wei; Chien, Chih-Te; Chiu, Wan-Ching; Lin, Shu-Yi
Abstract : A nucleus penetrating vehicle is indispensible when seeking to deliver plasmid DNA for gene transfection. Abstract : A nucleus penetrating vehicle is indispensible when seeking to deliver plasmid DNA for gene transfection. In this study, dendrimers with terminal thymine groups were synthesized to meet this objective. Through modifications of the hydrophilic and neutral thymine moieties on hyperbranched peripheries, these dendrimers can achieve biosafety, efficient endosomal escape ability, cytosolic accessibility, and eventually, nuclear entry for the purposes of gene transfection. After optimization of the thymine coverages, better gene expression can only be achieved while replacing ∼50% of the amine groups of a dendrimer with thymine moieties. Presumably, a specific dendrimer comprising thymine and primary amines might possess a synergistic effect to promote pDNA condensation via the cooperation of electrostatic interaction and hydrogen bonding. In comparison, a dendrimer entirely capped by thymine can lose external amines, decreasing pDNA complexity and stability, which would cause poor gene transfection. The utility of specific thymine-capped dendrimers in vivo level was demonstrated to successfully and efficiently deliver plasmid DNA at a low complex ratio into mouse muscle by intramuscular injection. Upon the easy accessibility of intramuscular administration, the capability of thymine-capped dendrimers might be potentially used in immunotherapeutic gene transfection in the future.